2002
DOI: 10.1097/01.mp.0000036342.73003.55
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase IIα Expression in Pituitary Adenomas and Carcinomas: Relationship to Tumor Behavior

Abstract: DNA topoisomerase II␣ (Topo II␣) is a molecular and immunohistochemical marker that indicates proliferation rate and is the target for several antineoplastic agents. The present immunohistochemical study of a large series of surgically removed pituitary tumors was designed to assess the prognostic significance of Topo II␣ expression relative to patient age, gender, tumor type and size, invasiveness, metastasis, MIB-1-labeling index and angiogenesis. Changes of Topo II␣ expression in the tumors treated with bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
4
31
2
Order By: Relevance
“…22,23 Because the histologic appearance of pituitary tumors is a poor predictor of aggressive behavior, 24 a number of studies have assessed cell proliferation and angiogenesis markers as predictors of tumor prognosis. [25][26][27][28][29] To obtain deeper insight into the role of COX-2 in pituitary tumor pathobiology, we analyzed the correlation between COX-2 expression and immunolabeling for MIB-1, a cell proliferation marker, as well as microvessel density (MVD), microvessel surface density (MSD), and expression of hypoxia-inducible factor-1␣ (HIF-1␣).…”
mentioning
confidence: 99%
“…22,23 Because the histologic appearance of pituitary tumors is a poor predictor of aggressive behavior, 24 a number of studies have assessed cell proliferation and angiogenesis markers as predictors of tumor prognosis. [25][26][27][28][29] To obtain deeper insight into the role of COX-2 in pituitary tumor pathobiology, we analyzed the correlation between COX-2 expression and immunolabeling for MIB-1, a cell proliferation marker, as well as microvessel density (MVD), microvessel surface density (MSD), and expression of hypoxia-inducible factor-1␣ (HIF-1␣).…”
mentioning
confidence: 99%
“…In order to treat patients more effectively, rather than to await confirmation of tumor recurrence by MR imaging, suitable markers of invasiveness and proliferation of pituitary adenomas are sought to select patients with atypical pituitary adenomas. In our group of 60 patients, 73% expressed Topo2A, against 76%, reported by Vidal et al [16].…”
Section: Discussionmentioning
confidence: 64%
“…Wolfsberger et al [17] found no dependence of Topo2A expression on tumor size, while Vidal et al [16] suggested a negative correlation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations